2000
DOI: 10.1203/00006450-200005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition during the First 2 Years of Life: An Updated Reference

Abstract: Normative body composition during the first 2 y of life was derived from a prospective study of 76 children. We present 1) fat free mass (FFM) and its components, and fat mass (FM), 2) incremental growth rates partitioned into chemical components, and 3) age-specific and gender-specific constants for converting chemical and physical components into FFM for children during the first 2 y of life. A multicomponent model based on measurements of total body water (TBW), total body potassium (TBK) and bone mineral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
379
7
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(422 citation statements)
references
References 12 publications
29
379
7
7
Order By: Relevance
“…On average, %TBF in the 9-month-old infants is similar to the corresponding figure presented by Davies et al (1997), but higher than that reported by Butte et al (2000a). Percentage TBF in the 14-month-old children is higher than corresponding figures presented by others for 12-month-old children (Davies et al, 1997;de Bruin et al, 1998;Butte et al, 2000a).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…On average, %TBF in the 9-month-old infants is similar to the corresponding figure presented by Davies et al (1997), but higher than that reported by Butte et al (2000a). Percentage TBF in the 14-month-old children is higher than corresponding figures presented by others for 12-month-old children (Davies et al, 1997;de Bruin et al, 1998;Butte et al, 2000a).…”
supporting
confidence: 68%
“…However, Butte et al (2000a) recently presented slightly different hydration factors. Applying these factors to our children resulted in slightly higher %TBF in all groups except in 14-month-old girls, where a 0.1% lower figure was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, no similar study is Figure 1 Comparison of body fatness obtained by the body water dilution method (%TBF-BWD) and by the skinfold technique (%TBF-SFT) according to Bland and Altman (1986) available for children in the age group studied in this paper. However, Butte et al (2000) have recently provided estimates of the degree of hydration in FFM for children under 2 y of age. The values reported for children between 3 months and 2 years are in close agreement with the corresponding values published by Fomon et al (1982), that is, those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For comparative purposes, for example, reference data on infant body composition were taken from the study of Butte et al (2000) in which TBW was determined by deuterium dilution, and ECW by TBW and total body potassium data and the known concentration of potassium in ECW compartment. It shows that during normal growth between 3 and 18 months, the ECW/TBW ratio effectively decreases, reflecting an increase in the intracellular mass with maturation, and also that the percentage of body fat decreases (Butte et al, 2000). In our study, the ECW/TBW ratio index decreased in the Control infants, as expected, while it increased on average in the Stunted-at-18 months group, the trend of the change already being apparent at age 7 months.…”
Section: Controls (N=170)mentioning
confidence: 99%